he heritage game - Alan Peacock (Oxford University Press, 2008)
A notable feature in cultural life is the growing demand to preserve and promote public access to historical buildings and sites, and artistic treasures of the past. Governments are increasingly involved in financing and regulating private attempts to meet this growing demand as well as extending their own provision of these treasures in state and locally owned museums and galleries. These developments raise important issues about the scope, content, and relevance of heritage policies in today's world. Written by two leading figures in the field of cultural economics, this authoritative book focuses on the impact of economic analysis on the formulation and implementation of heritage policy